Rancang Bangun Sistem Informasi E-Commerce Penjualan Ayam Pedaging Berbasis Website di Kabupaten Manggarai Barat, NTT - Kevin Imanto Krisenda Resman; Ida Bagus Putu Gunadnya; I Putu Gede Budisanjaya (Jurnal BETA (Biosistem dan Teknik Pertanian), 2021)
Broiler chicken sales in the West Manggarai Regency are still done traditionally. Traditional broiler chicken marketing is considered ineffective in the current digitalization era because many businesses have directed to the digital world, one of which is an online sales system or e-commerce. The purpose of this research was to design a system of selling broilers chicken online so that it can connect to farmers and buyers in the digital world. Broiler chicken e-commerce the system was built in the form of a website to facilitate users accessing the system without has to install applications and get free access. The system was built using Laravel framework version 5.8 and the XAMPP application as a database server. System testing used the black box testing and user acceptance testing (UAT). Black box testing focuses on the functional requirements of the software, while UAT testing focuses on non-functional requirements. Results of UAT test revealed the percentage of user acceptance of software that had been made. The results of the system testing using the black box testing method indicated that the system met the expectations of the users. UAT tests result obtained score interpretation score which value of 80.53%. This showed that the percentage of user acceptance of website-based broiler chicken sales information system in West Manggarai Regency, East Nusa Tenggara that had been built got the very good category.